2014
DOI: 10.5935/0103-507x.20140059
|View full text |Cite
|
Sign up to set email alerts
|

Septic versus non-septic acute kidney injury in critically ill patients: characteristics and clinical outcomes

Abstract: ObjectiveThis study aimed to describe and compare the characteristics and clinical outcomes of patients with septic and non-septic acute kidney injury.MethodsThis study evaluated an open cohort of 117 critically ill patients with acute kidney injury who were consecutively admitted to an intensive care unit, excluding patients with a history of advanced-stage chronic kidney disease, kidney transplantation, hospitalization or death in a period shorter than 24 hours. The presence of sepsis and in-hospital death w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 38 publications
2
36
2
Order By: Relevance
“…18 Despite more patients with septic AKI required RRT when compared with non-septic AKI, they had better renal recovery. This finding is actually similar to that reported by Cruz et al and Bagshaw et al, 8,19 signifying a difference in the pathophysiology [20][21][22] between septic and non-septic AKI. Instead, Singer et al proposed the cell cycle arrest hypothesis and mentioned that multiorgan failure induced by critical illness is primary a functional, rather than structural abnormality.…”
Section: Discussionsupporting
confidence: 81%
“…18 Despite more patients with septic AKI required RRT when compared with non-septic AKI, they had better renal recovery. This finding is actually similar to that reported by Cruz et al and Bagshaw et al, 8,19 signifying a difference in the pathophysiology [20][21][22] between septic and non-septic AKI. Instead, Singer et al proposed the cell cycle arrest hypothesis and mentioned that multiorgan failure induced by critical illness is primary a functional, rather than structural abnormality.…”
Section: Discussionsupporting
confidence: 81%
“…, Zang & Yan , Cruz et al . ). Renal failure in sepsis is characterized by decreased GFR, often estimated by increased plasma creatinine, and oliguria/anuria (Angus & van der Poll ).…”
Section: Sepsis and Akimentioning
confidence: 97%
“…Sepsis is the most common cause of AKI in intensive care units, and in combination, sepsis and severe renal dysfunction constitute a major risk of dying (50-65% 90-day mortality) (Bagshaw et al 2007, Zang & Yan 2013, Cruz et al 2014. Renal failure in sepsis is characterized by decreased GFR, often estimated by increased plasma creatinine, and oliguria/ anuria (Angus & van der Poll 2013).…”
Section: Sepsis and Akimentioning
confidence: 99%
“…Similar finding noticed by Marilla et al that sepsis is independent predictor of death. 22 In our study, requirement of mechanical ventilation was found to be an independent predictor of mortality in critically ill children admitted in PICU with AKI. Though MODS, requirement of renal replacement therapy and metabolic acidosis predicted mortality on univariate analysis, they were eliminated on multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 47%